Determinación de las competencias organizacionales en las avícolas en los cantones Jipijapa, Santa Ana y 24 de Mayo - Paz Álava, Rogger Eduardo (2021)
The objective of this research was to determine the organizational competencies of poultry MSMEs in the cantons of Jipijapa, 24 de Mayo and Santa Ana. The types of research with which they worked were: field, bibliographic and descriptive research, which were oriented in a mixed quali-quantitative approach and the inductive, deductive and Delphi method was defeated; In this process, techniques such as the interview, survey and cluster analysis were applied, the first two to collect information and the last to perform the cluster sampling. Twenty-two poultry were characterized through a semi-structured interview with the managers or managers, from which the information necessary to initiate the investigation was extracted; After this, the homogeneous groups were determined through the cluster analysis and the sample was calculated. Next, the procedure for the identification of organizational competencies was applied, which consisted in creating the group of experts through the Delphi method, and with their judgment, these competencies were determined, which were subjected to evaluation and the gap, which led to an organizational skills manual and a proposal for improvement actions. One of the points that he undoubtedly highlighted is that 68.18% of the poultry farms lack strategic analysis and that men occupy 100% of the managerial positions and the identification of the organizational competencies resulted in that the competencies do not they were at the desired level.